Low Prevalence of ETV6::RUNX1 Fusion Gene in a Hispanic Population - Minerva Mata-Rocha; Angelica Rangel-López; Elva Jimenez-Hernandez; Juan Carlos Nuñez-Enríquez; Blanca Angélica Morales-Castillo; Norberto Sánchez-Escobar; Norberto Sánchez-Escobar; Omar Alejandro Sepúlveda-Robles; Juan Carlos Bravata-Alcántara; Alan Steve Nájera-Cortés; María Luisa Pérez-Saldivar; Janet Flores-Lujano; et al. (Frontiers Media S.A., 2022)
ETV6::RUNX1 is a genetic rearrangement of good prognosis in children with acute lymphoblastic leukemia (ALL). In Mexico, its prevalence is low in comparison with Caucasian populations. We developed a novel TaqMan one-step RT-qPCR approach to assess the prevalence of four genetic rearrangements in a cohort of Hispanic children with ALL from Mexico City. The prevalence of common fusion gene transcripts was as follows: TCF3::PBX1 7.7%; BCR::ABL1p190 3.3%; and KMT2A::AFF1 2.8%, and ETV6::RUNX1was observed with low prevalence (10.5%) in comparison to that reported for developed countries. This is consistent with previous findings on Mexican children with ALL and similar to those reported on children from Hispanic populations. The confirmation of a low prevalence of ETV6::RUNX1 in children of a Hispanic origin represents an advancement in the description of genetic factors of ALL in these populations.